Analisis Yuridis Putusan Nomor 811 K/Pdt.Sus-Hki/2021 Tentang Sengketa Merek Yang Memiliki Persamaan Pada Pokoknya - Arif Prasetyo, Muhammad; Rodiatun Adawiyah; Mahulae, Rivka Natauli; Masniar Nainggolan (Unram Law Review, 2024)
Brand similarities are regulated in brand law which often occurs in various places, especially in Indonesia. Based on this research, these similarities are in the form of similar image elements, similar sounds, similar letters or words, names, numbers, colors, etc. in the form of an arrangement or combination of the arrangement of these elements, whether in the form of goods or services, whether dissimilar or similar and based on general public knowledge, the quality of the mark obtained due to holding very large promotions and followed by proof of registration of the mark itself in various country.This research aims to understand the types of brand violations that have fundamental similarities with other brands and to find out the sanctions that will be given to perpetrators who commit similarities with other brands. This research also aims to understand the legal consequences for perpetrators who use brands that have fundamental similarities with other brands. This study uses a normative or doctrinal method and uses a statute and conceptual approach. The study concluded that The Timberlake brand had violated the Brand Law, namely by having essential resembles with the Timberland brand, which includes pronunciations, product classification, and visual aspects. The judge’s verdict was that the Timberlake was guilty of Trademark violation and was obliged to compensate the plaintiff